Brain-targeted drug delivery - nanovesicles directed to specific brain cells by brain-targeting ligands - Moreira, Ricardo (2024)
Neurodegenerative diseases are characterized by extensive loss of function or death of brain cells, hampering the life quality of patients. Brain-targeted drug delivery is challenging, with a low success rate this far. Therefore, the application of targeting ligands in drug vehicles, such as lipid-based and polymeric nanoparticles, holds the promise to overcome the blood-brain barrier (BBB) and direct therapies to the brain, in addition to protect their cargo from degradation and metabolization. In this review, we discuss the barriers to brain delivery and the different types of brain-targeting ligands currently in use in brain-targeted nanoparticles, such as peptides, proteins, aptamers, small molecules, and antibodies. Moreover, we present a detailed review of the different targeting ligands used to direct nanoparticles to specific brain cells, like neurons (C4-3 aptamer, neurotensin, Tet-1, RVG, and IKRG peptides), astrocytes (Aquaporin-4, D4, and Bradykinin B2 antibodies), oligodendrocytes (NG-2 antibody and the biotinylated DNA aptamer conjugated to a streptavidin core Myaptavin-3064), microglia (CD11b antibody), neural stem cells (QTRFLLH, VPTQSSG, and NFL-TBS.40–63 peptides), and to endothelial cells of the BBB (transferrin and insulin proteins, and choline). Reports demonstrated enhanced brain-targeted delivery with improved transport to the specific cell type targeted with the conjugation of these ligands to nanoparticles. Hence, this strategy allows the implementation of high-precision medicine, with reduced side effects or unwanted therapy clearance from the body. Nevertheless, the accumulation of some of these nanoparticles in peripheral organs has been reported indicating that there are still factors to be improved to achieve higher levels of brain targeting. This review is a collection of studies exploring targeting ligands for the delivery of nanoparticles to the brain and we highlight the advantages and limitations of this type of approach in precision therapies.